2016
DOI: 10.1016/j.healthplace.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Rural tobacco use across the United States: How rural and urban areas differ, broken down by census regions and divisions

Abstract: This project compared urban/rural differences in tobacco use, and examined how such differences vary across regions/divisions of the U.S. Using pooled 2012–2013 data from the National Survey on Drug Use and Health (NSDUH), we obtained weighted prevalence estimates for the use of cigarettes, menthol cigarettes, chewing tobacco, snuff, cigars, and pipes. NSDUH also provides information on participants’ residence: rural vs. urban, and Census region and division. Overall, use of cigarettes, chew, and snuff were hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
127
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(136 citation statements)
references
References 22 publications
(27 reference statements)
7
127
0
2
Order By: Relevance
“…11 For example, in a recent study using national data, the prevalence of rural daily cigarette use was 16.3%, whereas the prevalence of urban use was 12.3%. 12 Rural past-30-day use of cigarettes and smokeless tobacco were also higher, although there were no urban/rural differences at the national level for use of menthol cigarettes, cigars, or pipes. 12 Other work examining national trends from 2007–2014 has shown that although there is a declining cigarette smoking rate in the U.S., the decline is more pronounced for urban than for rural populations.…”
Section: Introductionmentioning
confidence: 89%
“…11 For example, in a recent study using national data, the prevalence of rural daily cigarette use was 16.3%, whereas the prevalence of urban use was 12.3%. 12 Rural past-30-day use of cigarettes and smokeless tobacco were also higher, although there were no urban/rural differences at the national level for use of menthol cigarettes, cigars, or pipes. 12 Other work examining national trends from 2007–2014 has shown that although there is a declining cigarette smoking rate in the U.S., the decline is more pronounced for urban than for rural populations.…”
Section: Introductionmentioning
confidence: 89%
“…It is therefore perhaps not too surprising that rural residents often exhibit higher prevalence of health-related risk behaviors, and higher mortality rates than their urban counterparts (Mansfield et al, 1999; National Center for Health Statistics, 2012; Pettit and Nienhaus, 2010; Rural Health Reform Policy Research Center, 2014). In particular, cigarette smoking prevalence is higher among rural versus urban residents (American Lung Association, 2012; Doescher et al, 2006; Roberts et al, 2016; Rural Health Reform Policy Research Center, 2014), a pattern that has been observed for at least the last two decades (Eberhardt et al, 2001), and warrants ongoing monitoring. The present study was conducted in response to a dearth in recent research monitoring and comparing time trends in cigarette smoking prevalence between urban and rural populations in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Given the limited set of covariates used by Droescher and colleagues (2006), and the lack of controls in a visual comparison of unadjusted (except for age) plots from the chartbooks, it remains unclear whether there is a unique contribution from rural residence on cigarette use after controlling for a comprehensive set of potentially confounding covariates including outdoor labor (Matz et al, 2015), marital status (Lindström, 2010), substance abuse and mental health variables (Substance Abuse and Mental Health Services Administration, 2013), health insurance (Centers for Disease Control and Prevention, 2015), and smokeless tobacco use (Roberts et al, 2016), all of which are related to tobacco use, could vary between urban and rural populations, and should be controlled in a comparative rural versus urban analysis in addition to variables included in similar previous work (Droescher, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…[6] Rural residence has been shown to be an independent predictor of this difference in smoking trends, even after controlling for important covariates. [6,7] The geographic disparity in smoking rates has been found to be greater for women than for men. [8] Understanding this geographic disparity and reducing the higher rates of smoking among rural Americans has been acknowledged as a public health priority.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Rural populations and cultures are heterogeneous, as are the challenges they face when it comes to quitting tobacco. [7,11] Among these are barriers to treatment access, including lack of insurance, [12] geographical isolation, and limited access to trained tobacco treatment providers.…”
Section: Introductionmentioning
confidence: 99%